Age-related increases in false recognition: the role of perceptual and conceptual similarity - Pidgeon, Laura M.; Morcom, Alexa M. (Frontiers in Aging Neuroscience, 2014)
Older adults are more likely to falsely recognize novel events than young adults, and recent behavioral and neuroimaging evidence points to a reduced ability to distinguish overlapping information due to decline in hippocampal pattern separation. However, other data suggest a critical role for semantic similarity. Koutstaal et al. [(2003). False recognition of abstract versus common objects in older and younger adults: Testing the semantic categorization account, J. Exp Psychol. Learn, 29(4), 499-510] reported that older adults were only vulnerable to false recognition of items with pre-existing semantic representations. We replicated Koutstaal et al.’s (2003) second experiment and examined the influence of independently rated perceptual and conceptual similarity between stimuli and lures. At study, young and older adults judged the pleasantness of pictures of abstract (unfamiliar) and concrete (familiar) items, followed by a surprise recognition test including studied items, similar lures, and novel unrelated items. Experiment 1 used dichotomous ‘old/new’ responses at test, while in Experiment 2 participants were also asked to judge lures as ‘similar’, to increase explicit demands on pattern separation. In both experiments, older adults showed a greater increase in false recognition for concrete than abstract items relative to the young, replicating Koutstaal et al.’s (2003) findings. However, unlike in the earlier study, there was also an age-related increase in false recognition of abstract lures when multiple similar images had been studied. In line with pattern separation accounts of false recognition, older adults were more likely to misclassify concrete lures with high and moderate, but not low degrees of rated similarity to studied items. Results are consistent with the view that older adults are particularly susceptible to semantic interference in recognition memory, and with the possibility that this reflects age-related decline in pattern separation.